Modern Understanding of Variety Vocal Arts in 1970s – 1980s - Altunina V. V. (Development of Modern Competencies of Teachers and Students through the Study and Popularization of the Traditional Culture of the Peoples of the Russian Federation, 2021)
this article provides an analysis of the main processes in the soviet variety vocal art in the 1970s and 1980s. The research of the soviet variety vocals in this time period is significant to form an objective view of the nature of the Russian variety in present day. The purpose of this essay is in reviewing the changes of the soviet and Russian variety emotional content as a significant part of its development and to determine its nature.
Keywords: искусство; жанр; art; эстрадная песня; эстрадное вокальное искусство; музыкальная культура; variety vocal art; musical culture; variety song; genre